Genome-wide profiling in treatment-naive early rheumatoid arthritis reveals DNA methylome changes in T and B lymphocytes - Glossop, John R.; Emes, Richard D.; Nixon, Nicola B.; Packham, Jon C.; Fryer, Anthony A.; Mattey, Derek L.; Farrell, William E. (Future Medicine, 2016)
AIM: Although aberrant DNA methylation has been described in rheumatoid arthritis (RA), no studies have interrogated this epigenetic modification in early disease. Following recent investigations of T- and B-lymphocytes in established disease, we now characterize in these cell populations genome-wide DNA methylation in treatment-naive patients with early RA. PATIENTS & METHODS: HumanMethylation450 BeadChips were used to examine genome-wide DNA methylation in lymphocyte populations from 23 early RA patients and 11 healthy individuals. RESULTS: Approximately 2000 CpGs in each cell type were differentially methylated in early RA. Clustering analysis identified a novel methylation signature in each cell type (150 sites in T-lymphocytes, 113 sites in B-lymphocytes) that clustered all patients separately from controls. A subset of sites differentially methylated in early RA displayed similar changes in established disease. CONCLUSION: Treatment-naive early RA patients display novel disease-specific DNA methylation aberrations, supporting a potential role for these changes in the development of RA.